2020
DOI: 10.1080/0907676x.2020.1803376
|View full text |Cite
|
Sign up to set email alerts
|

The use of resources for legal terminological decision-making: patterns and profile variations among institutional translators

Abstract: Effective information mining for legal terminological research in translation is largely determined by the ability to contextualize concepts in their legal framework and to resort to relevant legal sources. Specialized knowledge of these sources thus emerges as a competence marker that is expected to converge with that of comparative law practitioners. Against this background, a survey was conducted in order to examine institutional translators' use of resources for translation in general and their perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In comparison, students with a low level of self-efficacy may experience more uncertainty and stress during the process (e.g., Bolaños-Medina, 2014;Araghian et al, 2018). As a result, such anxiety can, in turn, bring about additional strain to adjust their strategies and make more improvements in their translation products (Rojo and Caro, 2016;Prieto Ramos, 2020;Sycz-Opoń, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, students with a low level of self-efficacy may experience more uncertainty and stress during the process (e.g., Bolaños-Medina, 2014;Araghian et al, 2018). As a result, such anxiety can, in turn, bring about additional strain to adjust their strategies and make more improvements in their translation products (Rojo and Caro, 2016;Prieto Ramos, 2020;Sycz-Opoń, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In translation studies, online information seeking has been found to be significantly correlated with translation process (e.g., Hvelplund, 2019;Sycz-Opoń, 2019;Prieto Ramos, 2020). Previous studies have shown that online resources such as search engines, electronic dictionaries, and specific portals, as compared with seeking information from print resources, enable translators to acquire better information in a more efficient way when they experience uncertainty in the problem-solving process (e.g., Hvelplund, 2017;Kuznik and Olalla-soler, 2018;Whyatt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first preliminary step consisted of verifying the relevance of LTC in institutional translation settings by examining the volumes and genres of translated texts in several EU and intergovernmental organisations (IGOs) (Prieto Ramos and Guzmán 2021 ), and by crossing this data with those obtained in a survey of institutional translators (from 12 organisations) (Prieto Ramos 2020 ) and in 33 structured interviews with 45 service heads and quality advisers. The correlative analysis of this data corroborated that legal (and administrative) translation in a broad sense (including law- and policy-making, implementation monitoring, adjudication and administrative functions) is the most prominent commonly-shared translation specialisation at international organisations from a quantitative and a qualitative perspective.…”
Section: Towards An Updated Competence Model For Institutional Transl...mentioning
confidence: 99%
“…66 When faced with ambiguities or difficulties during translation, translators can find feasible and quick solutions with the help of electronic dictionaries, online knowledge-sharing platforms, and search engines. 67,68 The introduction of the internet has also dramatically expanded the information sources accessible to translators, transformed the way of searching for information in translation activities, and improved the effectiveness and efficiency of the information-seeking process. 69,70…”
Section: Dovepressmentioning
confidence: 99%